2010
DOI: 10.1111/j.1439-0396.2009.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and nitrogen utilization in sheep fed enset (Ensete ventricosum) pseudostem or corm and graded levels of Desmodium intortum hay to wheat straw-based diets

Abstract: The aim of this study was to investigate the effects of different levels of Desmodium intortum (Desmodium) hay supplementation in sheep fed fixed amounts of enset pseudostem or corm and a basal diet of wheat straw on intake, digestibility and nitrogen utilization. Eighteen male sheep with a mean (± SD) live weight of 20.5 ± 1.45 kg were assigned to six treatments in a completely randomized design and fed either 108 g dry matter (DM) enset pseudostem or 165 g DM enset corm each with three levels (100, 200 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The possible loss of some leaf material that is generally higher in CP and tannins content than the stems during hay making and transportation could have also contributed to the rather low CP content (Kumar and Vaithiyanathan, 1990). The other chemical composition parameters such as NDF and ADF of the Desmodium intortum hay, though in line with what is reported elsewhere in literature (Perez-Maldonado and Norton, 1996;Kariuki et al, 1999;Kariuki et al, 2001;Nurfeta, 2010), were on the higher end. The PSC content of the leguminous hay (3.5% DM TT and 3.0% DM CT) agreed with findings by Perez-Maldonado and Norton (1996) who reported 3.2% DM CT and Tolera and Sundstol (2000) who reported 3.5% DM TT for Desmodium intortum hay.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The possible loss of some leaf material that is generally higher in CP and tannins content than the stems during hay making and transportation could have also contributed to the rather low CP content (Kumar and Vaithiyanathan, 1990). The other chemical composition parameters such as NDF and ADF of the Desmodium intortum hay, though in line with what is reported elsewhere in literature (Perez-Maldonado and Norton, 1996;Kariuki et al, 1999;Kariuki et al, 2001;Nurfeta, 2010), were on the higher end. The PSC content of the leguminous hay (3.5% DM TT and 3.0% DM CT) agreed with findings by Perez-Maldonado and Norton (1996) who reported 3.2% DM CT and Tolera and Sundstol (2000) who reported 3.5% DM TT for Desmodium intortum hay.…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in feed intake was accompanied by a reduction in CP apparent digestibility suggesting a possible suboptimal microbial activity in the rumen resulting in slow digestion playing a part in this. Several previous studies supplementing low quality basal diets offered to ruminants with Desmodium intortum reported no effect of feeding the legume on intake (Kariuki et al, 1999;Nurfeta, 2010), even at higher inclusion level (66%) than used in the present study (Tolera and Sundstol, 2000). Our finding, however, was in agreement with other studies where ruminants fed on diets rich in tannins also decreased feed intake (Grainger et al, 2009: Acacia mearnsii supplementation with dietary CT levels of 0.9 and 1.5% DM; Dschaak et al, 2011: supplementation with Quebracho tannin extract resulting in 3% DM dietary CT).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, consumption of low-quality roughages such as straw and poor grass hay can be increased markedly by the addition of protein supplements. Ruminant livestock production is hindered by inadequacy and low quality of feed [10] as well as high level of productivity cannot be obtained since the tropical grasses which are usually given to these livestock are low or deficient in protein [11]. It has however been reported that, when these tropical grasses are supplemented with concentrates, their intake and digestibility are improved [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ruminant livestock production is hindered by inadequacy and low quality of feed [10] as well as high level of productivity cannot be obtained since the tropical grasses which are usually given to these livestock are low or deficient in protein [11]. It has however been reported that, when these tropical grasses are supplemented with concentrates, their intake and digestibility are improved [10]. In fact, smallholder livestock farmers rarely adopt such strategies because these farmers consider concentrates as scarce and expensive to use.…”
Section: Introductionmentioning
confidence: 99%
“…e ruminant livestock production system is hindered by inadequacy and low quality of feed. A high level of productivity cannot be obtained since the tropical grasses which are usually fed to this livestock are inherently low in protein [1]. Likewise, the cereal straws and native grass hay commonly used as a roughage feed source for dairy animals in the present study area were observed to contain considerably low CP, in vitro organic matter digestibility, and higher levels of detergent fibers [2].…”
Section: Introductionmentioning
confidence: 99%